2011
DOI: 10.1002/gj.1300
|View full text |Cite
|
Sign up to set email alerts
|

U‐Pb zircon geochronology of granites and charnockite from southern India: implications for magmatic pulses associated with plate tectonic cycles within a Precambrian suture zone

Abstract: The Palghat-Cauvery Suture Zone (PCSZ) in southern India marks the trace along which continental blocks were sutured during the Precambrian. We report here U-Pb geochronological data based on laser ablation ICP mass spectrometry for zircons in two granite plutons and an associated charnockite from within the PCSZ. The weighted mean of 206 Pb/ 238 U ages for a rapakivi granite from the southern part of the PCSZ yields 819 AE 26 Ma (error: 2s; N ¼ 13). On the other hand, a metamorphosed A-type granite and a char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Pudukkottai, however, is not the only region to have such charnockite-granite association within the Madurai Block. Similar types of charnockite associated with A-type pink-granite near Ayyermalai from the northern (Sato et al 2011) and near Mottamalai (Rajapalayam) in the southern parts of the Madurai Block (George et al 2015) were reported earlier.…”
Section: Geological Settingsupporting
confidence: 52%
See 2 more Smart Citations
“…Pudukkottai, however, is not the only region to have such charnockite-granite association within the Madurai Block. Similar types of charnockite associated with A-type pink-granite near Ayyermalai from the northern (Sato et al 2011) and near Mottamalai (Rajapalayam) in the southern parts of the Madurai Block (George et al 2015) were reported earlier.…”
Section: Geological Settingsupporting
confidence: 52%
“…There have been a few reports of the early-to mid-Neoproterozoic ages now from the Madurai Block (Sato et al 2011;Teale et al 2011;Anderson et al 2012;Brandt et al 2014), since Santosh et al (2009) made the compilation indicating a gap between early-Paleoproterozoic and late-Neoproterozoic (see figure 7 of Santosh et al 2009). The available geochronological dataset indicates significant events during early to mid-Neoproterozoic period within the Madurai Block, though their importance in the broader framework of Wilson cycle, as proposed by Santosh et al (2009) is yet to be established.…”
Section: Geological Settingmentioning
confidence: 95%
See 1 more Smart Citation
“…Considering the available age data for the host rocks of the BIFs of the CSZ, it is evident that the majority of the iron formations belong to Neoarchean age Yellappa et al, 2012;Saitoh et al, 2011;Sato et al, 2011b;Noack et al, 2013;Clark et al, 2009;Ghosh et al, 2004. ) with the exception of the Cryogenian rock suite in the MOC Sato et al, 2012;Teale et al, 2011). It is also well established that the Neoarchean as well as Neoproterozoic subduction-accretion events and convergent margin tectonics must have been the hall marks of the CSZ.…”
Section: Timing Of Bif Formation and Tectonic Settingmentioning
confidence: 96%
“…Moving to the southern domain of the Indian Precambrian, the Palghat‐Cauvery Shear/Suture Zone marks an important crustal suture that divides the Archaean Dharwar Craton and the Proterozoic collage of crustal blocks. Sato et al () demonstrate major crust building magmatic activities in the Neoarchaean, mid Neoproterozoic magmatism associated with subduction of the Mozambique oceanic crust, followed by latest Neoproterozoic high‐grade metamorphism and magmatism associated with the assembly of Gondwana. This study establishes a protracted magmatic history in this region related to the Wilson Cycle of the Mozambique Ocean.…”
mentioning
confidence: 97%